Strategies to Improve Skills to Write Stories: A Case Study in Universities in Tulungagung City - Nurhayati, Dwi Astuti; Djatmika, Djatmika (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The article discusses the quality of language exploitation performed by the students of the English Language Study Program in the City of Tulungagung in writing English text stories. The data was collected for 4 months, starting May up to August 2020 in IAIN Tulungagung campus in the sense of data collection, through the observation. This study used case study design and involves 43 Indonesian undergraduate students and who were majoring in English. Narrative texts produced by the students were collected to be analyzed using a qualitative approach. Two aspects becoming the focus of discussion are the text structure and the text texture. The former represents how discourse units are selected and arranged in accordance to the narrative format, while the latter is related to how grammar is exploited and how words are selected for the stories. The results show that most of the students are very good in selecting and arranging discourse unit to build the stories. Meanwhile, they still show weaknesses in constructing grammar and selecting words for the stories. In these areas, inferences from Indonesian and Javanese languages happen.